Effectiveness of Business License Renewal Services (NIB for MSMEs) Through the OSS System at the Investment and One-Stop Integrated Services Office of Denpasar City - Ni Nyoman Reseani; Sri Sulandari (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This research aims to analyze the effectiveness of business license extension services through the Online Single Submission (OSS) system at the Investment and Integrated One-Stop Service Office (DPMPTSP) of Denpasar City. OSS, as part of the digital transformation of public services, is designed to improve the efficiency, transparency, and accessibility of licensing services, particularly for Micro, Small, and Medium Enterprises (MSMEs). The research results indicate that administratively, the implementation of OSS has had a significant positive impact on the increase in the issuance of Micro and Small Business Licenses (IUMK), from 888 licenses in 2018 to 2,671 licenses in 2022. However, the effectiveness of the system is not yet optimal, marked by a realization of license achievements only reaching 89.03% of the target, and the continued high dependence of the community on manual assistance due to low digital literacyAnalysis using e-Government theory and the Design-Reality Gap from Heeks (2006) shows a gap between system design and the real capabilities of users. Identified barriers include limited access to technology, low technical understanding, and a lack of consistent support and socialization. Additionally, inadequate institutional capacity, minimal cross-sector integration, and still passive communication strategies also affect service effectiveness. Therefore, strengthening human resources, training in digital literacy, and developing an inclusive and adaptive service ecosystem are needed for OSS to truly function as an effective and equitable digital public service instrument. Keywords: Effectiveness, OSS, business licensing, MSMEs, e-government, Denpasar